SEA EXECUTIONS AS AN ALTERNATIVE SOLUTION TO ELIMINATING OF THE DEATH PENALTY AND MINIMIZING CRIME - Balthasar Watunglawar; Katarina Leba (SOSCIED, 2022)
The purpose of this study is to find, describe, and conduct a critical analysis of the Sea Execution and the Death Penalty. The research method used is philosophical hermeneutics. Data collected through observation, documentation, and interviews were described, interpreted, reflected, compared, and analyzed critically. The results of this study informed the perception that the death penalty was not effective in dealing with crime. The death penalty was a moral crime because it was against human rights. Life was a right. There was no right to die. Death was associated with the Creator or Ruler taking back what had been given to man. Whoever gave, he was the one who had the authority to take it. If God Almighty was believed to be the giver of life, then God was the one who had the right to take back that life. A natural death, without the intervention of other parties, was evidence of taking rights which was the authority of God. God had never delegated this authority to anyone, including the State. Therefore, the death penalty contradicted the ideology of the State and the 1945 Constitution, so could not be used as a legal tool in eradicating crime. The execution of the sea was a solution to abolish the death penalty, because God used the execution of the sea in saving and converting humans, even though it was seen from a certain perspective as God's way of eradicating evil. Execution of the sea respected the authority of God and had freed State from mral evil.